VALIDASI MODUL BEHAVIORAL ACTIVATION-UGM MODIFIED DALAM MENINGKATKAN MANAJEMEN DIRI PASIEN PENYAKIT GINJAL KRONIK DI PUSKESMAS - , Pramudita Tungga Dewi, Prof. Dra. Kwartarini Wahyu Yuniarti, M.Med. Sc., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The problem of self-management in patients with Chronic Kidney Disease (CKD) is an important thing to be addressed. One of the factors that may affect the problem is psychological condition of the patient. Behavioral Activation (BA) is a psychological treatment techniques based behavioral approach. The purpose of this study was to validate the module BA in improving self-management of patients with CKD. The method used in this study was a quasi experimental design with independent untreated control group pre-test and post-test. The subjects were 7 patients with CKD Sleman district health centers are divided into two groups: the experimental group (n=4) and control group (n=3). Data analysis was using quantitative analysis with ANACOVA test SPSS 16.0, and field notes as complementary data. The results showed that there were differences in the increase in self-management behavior of CKD patients significantly significantly between patients receiving treatment and untreated BA (sig. 0,001). It can be concluded that the BA module valid to improve self-management of patients with CKD.